If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
3-((4*x)/3) = 0
(-4/3)*x+3 = 0
3-4/3*x = 0 // - 3
-4/3*x = -3 // : -4/3
x = -3/(-4/3)
x = 9/4
x = 9/4
| 2x-6/5 | | (2/3)x=18 | | 8x-3[2-(4-4x)]= | | 4.38-3.9=14.544+1.2c | | -7y/-7=13-x/-7 | | 2x+33=77 | | 3-3[2-(6y-5)]= | | x/5-3.2=15.7 | | 5(8y-8)-(4y+7)= | | Y^2+9y+81= | | 185=-y+264 | | x+2x+17=23x-3x | | 2(4y-8)-(4y+6)= | | (6x^3+4x-5)+(-3x^3-7x^2+4)= | | -6-7=5x+1-4x | | 4+3x=10+5 | | 30x=-4 | | 4(2y-5)-(7y+5)= | | (2/5y+8)=1/4y-3/5 | | 30x=-42+38 | | 7-17=-5z | | 3(2x+1)+5(x-5)= | | x*3=21 | | 3(4x+2)+7(x-3)= | | 3/(5x-8)=2/(3x+5) | | 24x^2-62x-11=0 | | logx-log(x-3)=1 | | 6y-8x=48forx | | 3+2(4y-1)=9y+7 | | 2x^2+x-22=0 | | 3(2x+2)+6(x-2)= | | 2/3/4 |